The Role Of Product Quality, Service Quality, And Social Engagement In Mediating The Influence Of Brand Image On Gen Z Purchase Decisions At Corner Nyonya - Naili Rahma Yuliani; Sisno Riyoko; Mohamad Rifqy Roosdhani (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of brand image on purchasing decisions mediated by product quality, service quality, and social media engagement among Generation Z at Corner Nyonya. Corner Nyonya is a contemporary culinary outlet that offers modern-style healthy food and drinks such as Vietnamese spring rolls, vegetable salads, coffee, and non-coffee drinks with distinctive Gen Z flavors, as well as processed banana and honey jackfruit snacks with various topping variants. The phenomenon of the rise of healthy lifestyle-based culinary businesses and social media trends encourages the need for marketing strategies that focus not only on products, but also on brand image and digital interactions with young consumers. This study uses a quantitative approach with the Partial Least Square-Structural Equation Modeling (PLS-SEM) method. Data were collected through an online questionnaire using a Likert scale of 1–10 from 110 Generation Z respondents who had purchased products at Corner Nyonya. The results show that brand image has a significant effect on product quality, service quality, and social media engagement, and indirectly influences purchasing decisions through these three mediating variables. These findings emphasize the importance of building a strong brand image, maintaining consistent product and service quality, and utilizing social media as an effective means of interaction to improve purchasing decisions in the younger generation consumer segment..